N-point g-loop vertex for a free fermionic theory with arbitrary spin - Di Vecchia, P; Pezzella, F; Frau, M; Hornfeck, K; Lerda, A; Sciuto, S (1990)
We use the sewing procedure of the operator formalism to construct explicitly the N-point g-loop vertex VN; g for a free fermionic (b, c)-system with conformal weight (λ, 1 - λ). We show that this vertex has the structure we expect from geometrical arguments. We obtain also several geometrical objects, e.g. the holomorphic λ-differentials on an arbitrary Riemann surface, which turn out to be expressed as a Poincaré θ-series over all elements of the Schottky group. From VN; g we compute explicitly correlation functions for our system, finding agreement with the geometrical procedure.